Thermally induced movements in ice-wedge polygons, western arctic coast: a long-term study - MacKay, J. (Géographie physique et Quaternaire, 2000)
Abstract Thermally induced seasonal movements of the active layer and subjacent permafrost have been measured in numerous ice-wedge polygons that have varied in age, type, crack frequency, and topographic location. The field observations show that, in winter, thermal contraction, which is inward, is constrained or vanishes at the polygon centres but, in summer, thermal expansion, which is outward, is unconstrained at the ice-wedge troughs. Therefore, there tends to be a small net summer transport of the active layer, to varying depths, into the ice-wedge troughs. The movement has been observed in all polygons studied. The slow net transport of material into the ice-wedge troughs has implications for: permafrost aggradation and the growth of syngenetic wedges in some troughs; the palaeoclimatic reconstruction of some ice- wedge casts; and the interpretation of polygon stratigraphy based upon the assumption that the polygon material has accumulated in situ .